The Data of the Initial Motivation – a Valuable Source for the Development of the Course Content. A Case Study in the Group of Business Students - Daugule, Iveta; Kapenieks, Atis (International Journal of Engineering and Technology, 2018)
This study continues the authorsâ€™ previous search for key factors to determine the stickiness of different kinds of knowledge. In the authorsâ€™ opinion, identifying the stickiness of every type of knowledge in the e-course it is possible to create the optimal distribution of the intensity of time and study materials, paying more attention to the more complex knowledge, while promoting the acquisition of the free flow of knowledge with some tasks aimed at collaboration between students. Also, our previous study showed that individual motivation plays an important role in studentsâ€™ success. That is why the scope of this study embraces the link of students' personal characteristics with their behavior and achievements in a learning environment. In this study, we are looking for key features for the future development of a more advanced learning system. Our scope of this study embraces the aspects of studentâ€™s initial motivation â€“ how to ascertain, define and then use it for the development of the further learning content. Students were divided into three groups, according to their plans for engagement in business projects. The study was conducted in the course, thatâ€™s organized according to the blended learning delivery approach. Part of this course takes place in a classroom, while the other part is embedded in an electronic environment on an Open edX platform-based E-Learning environment.Â Â